Evolutionary Adaptation of Kluyveromyces marxianus NIRE-K3 for Enhanced Xylose Utilization - Sharma, Nilesh Kumar; Behera, Shuvashish; Arora, Richa; Kumar, Sachin (Frontiers in Energy Research, 2017)
The evolutionary adaptation was approached on the thermotolerant yeast Kluyveromyces marxianus NIRE-K3 at 45oC on xylose as a sole source of carbon for enhancement of xylose uptake. After 60 cycles, evolved strain K. marxianus NIRE-K3.1 showed comparatively 3.75-fold and 3.0-fold higher specific growth and xylose uptake rates, respectively than that of native strain. Moreover, the short lag phase was also observed on adapted strain. During batch fermentation with xylose concentration of 30 g l-1, K. marxianus NIRE-K3.1 could utilize about 96 % of xylose in 72 h and produced 4.67 and 15.7 g l-1 of ethanol and xylitol, respectively, which were 9.72-fold and 4.63-fold higher than that of native strain. Similarly, specific sugar consumption rate, xylitol and ethanol yields were 5.07-fold, 1.15-fold and 2.44-fold higher as compared to the native strain, respectively. The results obtained after evolutionary adaptation of K. marxianus NIRE-K3 show the significant improvement in the xylose utilization, ethanol and xylitol yields, and productivities. By understanding the results obtained, the significance of evolutionary adaptation has been rationalized, since the adapted culture could be more stable and could enhance the productivity.